ASSAY OF ACETYLCHOLINE ESTERASE ENZYME ACTIVITY BY TITRIMETRIC METHOD - JAYANTH A; GURUPRASAD R (International Journal of Pharma and Bio Sciences, 2014)
Acetylcholine esterase (EC 3.1.1.7) is an enzyme, actively involved in cleaving the ester bond found in the molecule acetylcholine (a neurotransmitter). The enzyme plays an important role in detecting a wide array of neurodegenerative disorders like Parkinson’s disease, Alzheimer’s disease and Huntington’s disorders. An easy and effective assay is required to monitor the enzyme activity; which we have achieved by establishing a titrimetric assay that helps in determining the activity of the enzyme. The assay involves the use of an alkali to neutralize the carboxylic acid moiety released by the activity of the esterase enzyme on the substrate. A chromogenic indicator is used to detect the end point.The enzyme activity values were checked in comparison with the values obtained from Ellman’s method. The values obtained from both Ellman’s and the titrimetric methods are in agreement when produced under similar lab conditions. The percentage difference between the values form the Ellman’s method and Titrimetric method for Zebrafish brain acetylcholine esterase enzyme was found to be 1.53% and for the RBC acetylcholine esterase it was found to be 1.60%.